2011
DOI: 10.1158/1078-0432.ccr-10-2987
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Trabectedin As a Single Agent or in Combination with Everolimus for Clear Cell Carcinoma of the Ovary

Abstract: Purpose: The objective of this study was to evaluate the antitumor efficacy of trabectedin in clear cell carcinoma (CCC) of the ovary, which is regarded as an aggressive, chemoresistant, histologic subtype.Experimental Design: Using 6 human ovarian cancer cell lines (3 CCC and 3 serous adenocarcinomas), the antitumor effects of trabectedin were examined in vitro, and we compared its activity according to histology. We next examined the antitumor activity of trabectedin in both cisplatin-resistant and paclitaxe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 36 publications
5
39
0
Order By: Relevance
“…Another potential avenue is the combination of targeted agents with effective cytotoxic agents, as targeting agents are generally cytostatic. Intriguing preclinical results suggest that trabectedin is the most effective of the existing cytotoxic agents against CCC, 37 and this may be enhanced by the addition of an mTOR inhibitor. This combination warrants further investigation in future clinical studies.…”
Section: Future Directionsmentioning
confidence: 99%
“…Another potential avenue is the combination of targeted agents with effective cytotoxic agents, as targeting agents are generally cytostatic. Intriguing preclinical results suggest that trabectedin is the most effective of the existing cytotoxic agents against CCC, 37 and this may be enhanced by the addition of an mTOR inhibitor. This combination warrants further investigation in future clinical studies.…”
Section: Future Directionsmentioning
confidence: 99%
“…The authors concluded that Trabectedin/PLD combination improved progression-free survival and overall response rate in patients displaying a platinum-free interval of more than 6 months, compared with patients receiving PLD alone (35,36). In a more recent preclinical study, it was shown that Trabectedin inhibited tumor growth in xenograft models of clear cell carcinoma of the ovary, which further shows its potential as either a first-line or second-line therapy for certain subgroups of ovarian neoplasms (37). As such, patients exhibiting high amounts of immune infiltration in tumors may benefit from agents targeting activated TAMs.…”
Section: Tumor-associated Macrophagesmentioning
confidence: 99%
“…Cisplatin activates the mTOR survival pathway in epithelial and clear-cell carcinoma ovarian cancer cells, which may counteract cisplatin-induced apoptosis and in turn lead to cisplatin resistance (14,15). The mTOR inhibitors, rapamycin and its analogs, including everolimus, efficiently enhance the therapeutic efficacy of platinum in clear-cell ovarian carcinoma cells (16,17). Therefore, mTOR is a promising therapeutic target for the treatment of ovarian cancer when combined with cisplatin.…”
Section: Introductionmentioning
confidence: 99%